Historia Katedry Prawa Finansowego Wydziału Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego - Miemiec, Wiesława; Pest, Przemysław (Wydawnictwo Uniwersytetu Wrocławskiego, 2015)
The article presents the history of the Department of Financial Law at the Faculty of Law, Administration and Economics of the University of Wrocław. The article presents the biographies with an indication of the most important scientific achievements of the former heads of the Department — Prof. Lesław Adam, Prof. Krystyna Jandy-Jendrośka, Prof. Marek Mazurkiewicz, Prof. Ryszard Mastalski and Prof. Eugenia Fojcik-Mastalska. The article also identifies the current personal composition of the Department of Financial Law and the directions of the scientific research conducted in the Department.
Keywords: Katedra Prawa Finansowego; Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego; historia